PENGUATAN MANAJEMEN SYARIAH SEBAGAI PENGEMBANGAN DALAM INDUSTRI BISNIS - Nur Fadilah; Moh. Uzeir Mustaqfirin; Ulya Ardhia Cayani Ahmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study examines the strengthening of sharia management as an aspect of development in the industrial sector. The industrial sector has seen substantial growth in recent years, in reaction to global demand for products and services compliant with sharia guidelines. Where the process to produce goods starts from processing raw materials, into semi-finished products which are then further processed into finished goods. However, to ensure sustainable growth and face future challenges, effective management from a sharia perspective is essential. This research aims to find out how strengthening sharia management can function as a development in the industrial sector. Qualitative methods were chosen to gather information from a variety of sources, such as literature reviews, interviews with industry experts, and analysis of company documents. Then, the information is analyzed using relevant qualitative analysis methods. The findings of the study show that strengthening sharia management can provide significant benefits in business development in the industrial sector. In conclusion, strengthening sharia management as a strategy for industrial business development is able to create long-term added value for the company, increase customer reputation and trust, and encourage substantial growth. Therefore, the advice for practitioners and decision-makers in the industry is to prioritize the effective implementation of sharia management in their business strategies, paying attention to aspects of ethics, quality, and innovation that are in line with sharia principles. Keywords: Sharia Management, Business Industry,